Manifestações da linguagem oral na produção escrita do gênero carta de apresentação: aspectos discursivos/textuais e didáticos. - Watthier, Luciane (2016)
This research focused on reflections about the theme oral language manifestations in writing discursive/textual and didactic aspects, which was motivated from the following questions: How students of the 5th year of Elementary School and the 1st year of graduation in Language Arts College configures the genre letter of presentation? What are the main manifestations of oral language in the writing of texts produced by the students of the 5th year of the early years? These marks tend to disappear in college? How do the teachers approach the manifestations of oral language in written texts in their pedagogical practice in classroom? How can we, teachers/researchers, contribute didactically with questions related to manifestations of oral language in the written? We aim, based on answers to these questions, built knowledge about how the manifestations of orality reveal themselves in the discourse/textual level and how we could contribute with the didactic approach about this theme. Therefore, our objective sustains itself in recognize how the manifestations of oral language, discourse/textual level, occur in the genre letter of introduction produced by students of the 5th year (Elementary School) and 1st year of Language Arts college to, based on this recognition, propose didactic referrals which explore this phenomenon. With the view to achieving the initial objective and answer the research questions, we sustain the investigation upon the dialogical conception (BAKHTIN, 2010[1979], 2005[1963] and BAKHTIN/VOLOCHINOV, 2004[1929] and 1926) and in the interactionism approach (GERALDI, 1984, 1997). It is an educational research entered on Applied Linguistics, qualitative, with description and critic-interpretative investigation. We propose to examine texts of discursive genre introduction letter produced by the students of the 5th year of the Elementary School of four small cities of the western of Paraná and in the 1st year of graduation in Language Arts of the State University of Paraná (UNIOESTE) building a comparative analysis in relation to the theme investigated. When we accomplish this study, we establish relations with the configuration in the thematic content, compositional construction and linguistic style, since discourse can not be unlinked from the texts. Finally, we present didactic-methodological referrals to work with this theme in the Portuguese language teaching. As a result of this investigation, we noticed that there is a sharp level of difficulties related to the comprehension of the linguistics aspects more suitable for each social context of production. Although these difficulties prevail in productions of Elementary School, they do not disappear in college. In this way, we pointed to a need of the enlargement towards the linguistic-discourse knowledge of the students, according to the social context they belong.